An Unusual Case of Metastatic Basal Cell Carcinoma of the Prostate: A Case Report and Literature Review - Dong, Shiqiang; Liu, Qing; Xu, Zihan; Wang, Haitao (Frontiers in Oncology, 2020)
Background: Prostate cancer is one of the most common cancers in men worldwide. However, the incidence of primary basal cell carcinoma (BCC) of the prostate is rare in clinical practice; moreover, there is no standard treatment for these patients, most of whom have a poor prognosis. Herein, we report a rare case of a patient with BCC of the prostate who developed metastasis after undergoing radical prostate resection and whose prognosis improved after treatment with etoposide. Case Presentation: A 62-year-old male patient with a history of seminoma was admitted complaining of intermittent gross hematuria for 1 month. Following a prostate biopsy, the patient was diagnosed with BCC of the prostate and was subjected to radical prostate resection and radiotherapy. Initially, the patient showed improvement in his symptoms and no recurrence of prostate BCC. Two years later, however, a chest computed tomography (CT) scan revealed lung nodules but no symptoms of BCC. Pathological examination combined with immunohistochemical staining of the nodules confirmed metastatic prostate BCC. Although chemotherapy with docetaxel and cisplatin was well-tolerated, it did not slow the disease progression. Next-generation sequencing revealed mutations in the ataxia telangiectasia-mutated (ATM), SWI/SNF related-matrix associated-actin dependent regulator of chromatin-subfamily b-member 1 (SMARCB1), and phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) genes. Targeted therapy was not administered to the patient because of financial limitations, and etoposide was administered instead. A 9-month follow-up chest CT scan showed that some nodules had almost disappeared. Conclusion: There is currently no standardized therapy for prostate BCC, and most patients have a poor prognosis. However, this patient with recurrent BCC after radical prostatectomy responded to etoposide. Radical prostatectomy and radiotherapy should still be used as first-line therapy; however, second-line treatment options are limited. Thus, etoposide may be an alternative choice other options are not available. Additional efforts are needed to develop consensus treatment plans and elucidate the molecular features of prostate BCC.